Kepemimpinan Perempuan di MIN se Kota Bandar Lampung - Ahmad Fauzan; Subandi Subandi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Women's leadership in MIN Bandar Lampung City is found in 7 out of 12 Madrasah Madrasah Ibtidaiyah Negeri (MIN), namely: MIN 1 Bandar Lampung, MIN 3 Bandar Lampung, MIN 6 Bandar Lampung, MIN 8 Bandar Lampung, MIN 9 Bandar Lampung, MIN 10 Bandar Lampung, and MIN 12 Bandar Lampung. From the leadership of the MIN heads in Bandar Lampung, not a few achieved academic and non-academic achievements at the city and provincial levels and had good madrasah performance, 4 of the 7 madrasas were accredited A and 3 madrasas were accredited B, all of the madrasah heads already had degrees masters (S2). Among the successes of women's leadership in MIN Bandar Lampung City are: first; management of leadership and power, second; leadership and conflict management, third; leadership and change manageme